Les nouveaux territoires urbains d’Afrique de l’Est - Dominique Harre; Hervé Gazel; François Moriconi-Ebrard (Territoire en Mouvement)
Urbanization is very recent in the nine countries presented in this article (Burundi, Djibouti, Eritrea, Ethiopia, Kenya, Uganda, Rwanda, Somalia, and Tanzania). Urban growth has been very fast too over the last three decades, and has given form to large urbanized territories in areas historically very densely populated and officially classified as rural. These territories are linked with metropolitan areas (Nairobi, Dar es salam, Bujumbura), secondary cities (Jinja, Bukoba, Mtwara), and conurbations of regional magnitude (Kenya). However, without proper statistical measurement, these new urban territories would remain unintelligible. The figures and conclusions presented here draws on a study conducted by the research program e-Geopolis, which measures urban sprawl at various geographical scales and locates population agglomerations, independently of official data. This original approach makes possible to provide a statistical measure of the “generalized urbanization” in progress around Bujumbura, Kisii, or Kisumu. A careful look at urban morphologies and territorial status is another essential step to better understand territorial dynamics at work. The complex urban forms observed, marked by a triple heterogeneity, (morphological, economic, administrative) suggest that the new urban territories may be strongly fragmented. Many include in their perimeters large commercial agricultural areas as well as large urbanized areas without development, a trend that goes against recent political schemes. These evolutions call for renewed views on the nature of urbanization in East Africa, although the magnitude of in situ urbanization against the role of metropolitan areas in the emergence and expansion of the new urban territories is still difficult to determine.